2001
DOI: 10.1677/joe.0.1710065
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of estrogen receptor alpha and beta in gastric epithelium and enteric neurons

Abstract: A sexual dimorphism in gastric acid secretion has been known for many years, with women secreting less acid (40%) than men. The mechanisms mediating this sex difference are unknown, but a role for estrogens is suggested from animal models. Two estrogen receptor (ER) subtypes, ER and ER , mediate genomic effects of estrogens, and mRNA for both subtypes has been detected in the rat stomach. The objective of this study was to determine the cellular distribution of ER and ER proteins in the rat stomach. ER and ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 41 publications
1
64
0
Order By: Relevance
“…Each trans-acting factor is encircled with a square. and sst2 (Halmos et al 2000, Campbell-Thompson et al 2001, Dougherty et al 2006, and in rodent central nervous system the arcuate nucleus expresses more sst2 in female than male (Shimizu et al 2005, Bouyer et al 2006. Since the expression of ERs is known to increase in progressed tumors (Deroo & Korach 2006), it is expected that the increased ER proteins may lead to induce the sst2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Each trans-acting factor is encircled with a square. and sst2 (Halmos et al 2000, Campbell-Thompson et al 2001, Dougherty et al 2006, and in rodent central nervous system the arcuate nucleus expresses more sst2 in female than male (Shimizu et al 2005, Bouyer et al 2006. Since the expression of ERs is known to increase in progressed tumors (Deroo & Korach 2006), it is expected that the increased ER proteins may lead to induce the sst2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ueyama et al (2002) clearly demonstrated that estrogen synthetase (aromatase) is expressed in gastric parietal cells of the rat stomach. Furthermore, Campbell-Thompson et al (2001) reported that ERa expression was found in the stomach mucosa of rats, and Singh et al (1997) also revealed the existence of ER mRNA and protein using Northern blot analysis and enzyme immunoassay in the human stomach mucosa. Taken together, these findings suggest that estrogen produced in the stomach regulates ghrelin gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…23 Fourth, gastric parietal cells appear to have a potent endocrine role in secreting estrogens. [24][25][26][27] Atrophy of the gastric mucosa, observed in patients infected with CagA-positive Helicobacter pylori, 28 reduces the number of gastric parietal cells and may decrease local production of estrogens. Estrogens produced in the stomach directly induce expression and production of ghrelin, 29,30 which appears to increase bone formation by osteoblasts.…”
Section: Introductionmentioning
confidence: 99%